2014
DOI: 10.1371/journal.pone.0101898
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of mAb G250-SPIO Molecular Magnetic Resonance Imaging Nanoprobe for the Specific Detection of Renal Cell Carcinoma In Vitro

Abstract: Molecular magnetic resonance imaging (mMRI) has been paid more and more attention for early diagnosis of cancer. A sensitive and specific mMRI probe plays the most important role in this technique. In this study, superparamagnetic iron oxide (SPIO) nanoparticles and mAb G250 were conjugated as mMRI probe for the detection of clear cell renal cell carcinoma (ccRCC) using 3.0-Tesla MRI in vitro. mAb G250 could specifically recognize carbonic anhydrase IX (CAIX) antigen overexpressed in ccRCC and the SPIO nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…UV-vis spectrum showed that AntiCD36 had a characteristic absorption peak at 277 nm compared with CMSN-NH 2 , a characteristic absorption peak of the antibody at 259 nm emerged for CMSN@Anti, indicating that AntiCD36 was successfully connected to the surface of CMSN. The blue shift of AntiCD36's absorption peak from 277 nm to 259 nm after modi cation on CMSN might be caused by a change in the force between the adjacent particles after the antibody binding to the nanoparticle [20]. FT-IR spectra showed that the Si-O-Si antisymmetric stretching vibration peak (1076.22 cm − 1 ) of mSiO 2 was observed in both CMSN@Anti and CMSN-NH 2 , showing that the connection of AntiCD36 did not affect the basic structure of CMSN-NH 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV-vis spectrum showed that AntiCD36 had a characteristic absorption peak at 277 nm compared with CMSN-NH 2 , a characteristic absorption peak of the antibody at 259 nm emerged for CMSN@Anti, indicating that AntiCD36 was successfully connected to the surface of CMSN. The blue shift of AntiCD36's absorption peak from 277 nm to 259 nm after modi cation on CMSN might be caused by a change in the force between the adjacent particles after the antibody binding to the nanoparticle [20]. FT-IR spectra showed that the Si-O-Si antisymmetric stretching vibration peak (1076.22 cm − 1 ) of mSiO 2 was observed in both CMSN@Anti and CMSN-NH 2 , showing that the connection of AntiCD36 did not affect the basic structure of CMSN-NH 2 .…”
Section: Discussionmentioning
confidence: 99%
“…UV-vis absorption spectra displayed that the CMSN@Anti increased the characteristic absorption peak of AntiCD36 at 259 nm. Such a blue shift of absorption peak of AntiCD36 (277 nm) might be caused by the change of the force between adjacent particles after the binding of nanoparticles to Antibody [20]. The zeta potential of CMSN was − 28.07 ± 0.5 mV and was changed to 24.47 ± 0.4 mV after amidation, as well as 8.63 ± 0.3 mV after further AntiCD36 conjugation.…”
Section: Structure and Characteristics Of Nmsmentioning
confidence: 99%
“…A study with 30 patients with suspected ccRCC undergoing zirconium-89-labeled girentuximab immunoPET was closed recently, and results are expected soon (NCT02883153). One in vitro study showed that conjugation of iron oxide nanoparticles and girentuximab as a molecular MRI probe for the detection ccRCC is feasible [84].…”
Section: Immuno-imaging Using Girentuximabmentioning
confidence: 99%
“… Lu et al (2014) conjugated the monoclonal antibody G250 and SPIO into molecular MRI probes for the in vitro detection of clear cell RCC (ccRCC) using a 3.0-Tesla MRI. An in vitro MRI study of ccRCC and control cells confirmed that the fabricated mAb G250-SPIO nanoprobe could be used as a specific marker for ccRCC cells ( Lu et al, 2014 ). Moreover, the nanoprobe could be easily conjugated with other antitumor drugs and imaging materials to achieve multimodal imaging and diagnostic treatment integration.…”
Section: Nanotechnology In Renal Cancermentioning
confidence: 99%